2021
DOI: 10.1007/s00703-021-00784-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing current and future spatiotemporal precipitation variability and trends over Uganda, East Africa, based on CHIRPS and regional climate model datasets

Abstract: The lack of reliable rainfall projection records remains a major challenge to Uganda. In the advent of extreme wetness or drought events, reliable rainfall estimates for local planning and adaptation are essential. The present study used two main datasets to conduct a historical analysis from 1981 to 2019, coupled with future projections under representative concentration pathway (RCP 8.5) for the period 2020-2050. Historical analysis revealed bimodal annual rainfall pattern for March-May (MAM) and September-N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 102 publications
5
40
1
Order By: Relevance
“…v2) blends 0.05° resolution satellite imagery with in-situ measurements toproduce a gridded value from 1981 to present. CHIRPS has been evaluated and utilized by a number of studies over East Africa (Dinku et al, 2018;Ayugi et al, 2019;Ngoma et al, 2021).…”
Section: Observed Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…v2) blends 0.05° resolution satellite imagery with in-situ measurements toproduce a gridded value from 1981 to present. CHIRPS has been evaluated and utilized by a number of studies over East Africa (Dinku et al, 2018;Ayugi et al, 2019;Ngoma et al, 2021).…”
Section: Observed Datasetsmentioning
confidence: 99%
“…This has posed pronounced consequences on the population. Past studies have reported an observed decrease in rainfall during MAM season and an increase during SON (Nsubuga et al, 2014;2017;Egeru et al, 2019;Ngoma et al, 2021). Nevertheless, SON rains have exhibited higher interannual variability as they are reported to be more influenced by global teleconnections (Saji et al, 1999;Ongoma et al, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…Nevertheless, the entire country was considered in a few other studies such as Ngoma et al . (2021), Kisembe et al . (2019), Jury (2018), Onyutha (2016a), and Nsubuga et al .…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such products include Global Precipitation Climatology Project (GPCP) (Adler et al ., 2018), Princeton Global Forcing (PGF) (Sheffield et al ., 2006), Climate Forecast System Reanalysis (CFSR) of the National Center for Environmental Prediction (NCEP) (Saha et al ., 2014), Climate Research Unit (CRU) Time series version 4.0 (Harris et al ., 2020), and Climate Hazards group Infrared Precipitation with Stations (CHIRPS) (Funk et al ., 2015). A number of recent studies (Hua et al ., 2019; Alfaro et al ., 2020; Martinez‐Cruz et al ., 2020; Mubialiwo et al ., 2020; 2021b; Ngoma et al ., 2021; Onyutha et al ., 2021) have made use of the reanalyses and/or satellite products. The increasing use of satellite or reanalyses products is largely attributed to their global coverage, fine spatial and temporal resolutions, and long‐term record periods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation